Hormonal regulation of female reproduction - Christensen, A. (2012)
Reproduction is an event that requires the coordination of peripheral organs with the nervous system to ensure that the internal and external environments are optimal for successful procreation of the species. This is accomplished by the hypothalamic-pituitary-gonadal axis that coordinates reproductive behavior with ovulation. The primary signal from the central nervous system is gonadotropin-releasing hormone (GnRH), which modulates the activity of anterior pituitary gonadotropes regulating follicle stimulating hormone (FSH) and luteinizing hormone (LH) release. As ovarian follicles develop they release estradiol, which negatively regulates further release of GnRH and FSH. As estradiol concentrations peak they trigger the surge release of GnRH, which leads to LH release inducing ovulation. Release of GnRH within the central nervous system helps modulate reproductive behaviors providing a node at which control of reproduction is regulated. To address these issues, this review focuses on several critical questions. How is the HPG axis regulated in species with different reproductive strategies? What internal and external conditions modulate the synthesis and release of GnRH? How does GnRH modulate reproductive behavior within the hypothalamus? How does disease shift the activity of the HPG axis.